Chronic administration of Abarema cochliacarpos attenuates colonic inflammation in rats - Silva, Maria Silene da; Sánchez-Fidalgo, Susana; Cárdeno, Ana; Talero, Elena; Silva, Marcelo Aparecido da [UNESP]; Vilegas, Wagner [UNESP]; Brito, Alba R. M. Souza; Lastra, Catalina A. de la (Sociedade Brasileira de Farmacognosia, 2011)
Inflammatory bowel diseases are characterized by a chronic clinical course of relapse and remission associated with self-destructive inflammation of the gastrointestinal tract. Active extracts from plants have emerged as natural potential candidates for its treatment. Abarema cochliacarpos (Gomes) Barneby & Grimes, Fabaceae (Barbatimão), is a native medicinal plant in to Brazil. Previously we have demonstrated in an acute colitis model a marked protective effect of a butanolic extract, so we decided to assess its anti-inflammatory effect in a chronic ulcerative colitis model induced by trinitrobenzensulfonic acid (TNBS). Abarema cochliacarpos (150 mg/day, v.o.) was administered for fourteen consecutive days. This treatment decreased significantly macroscopic damage as compared with TNBS. Histological analysis showed that the extract improved the microscopic structure. Myeloperoxidase activity (MPO) was significantly decreased. Study of cytokines showed that TNF-α was diminished and IL-10 level was increased after Abarema cochliacarpos treatment. In order to elucidate inflammatory mechanisms, expression of cyclooxygenase (COX)-2 and nitric oxide synthase (iNOS) were studied showing a significant downregulation. In addition, there was reduction in the JNK and p-38 activation. Finally, IκB degradation was blocked by Abarema cochliacarpos treatment being consistent with an up-regulation of the NF-kappaB-binding activity. These results reinforce the anti-inflammatory effects described previously suggesting that Abarema cochliacarpos could provide a source for the search for new anti-inflammatory compounds useful in ulcerative colitis treatment.
Keywords: Abarema cochliacarpos; chronic colitis; inhibitor protein kappa B; JNK; p-38; trinitrobenzensulfonic acid